Temporal trends in all-cause mortality according to smoking status: Insights from the Global Registry of Acute Coronary Events. (1st September 2016) - Arbel, Yaron; FitzGerald, Gordon; Yan, Andrew T.; Tan, Mary K.; Fox, Keith A.A.; Gore, Joel M.; Steg, Ph. Gabriel; Eagle, Kim A.; Brieger, David; Montalescot, Gilles; Budaj, Andrzej; Lopez-Sendon, Jose; et al.
Abstract: Objective: Smoking has been shown to be a risk factor for heart disease. However, it was recently reported that despite the evolution in therapy for acute coronary syndrome (ACS), smokers have not demonstrated improved outcomes. The aim of the present study was to evaluate the temporal trends in the treatments and outcomes across a broad spectrum of ACS patients (STEMI and non-ST-elevation ACS [NSTEACS]) according to smoking status on presentation in the Global Registry of Acute Coronary Events (GRACE). Methods: Our cohort was stratified into 3 groups: current smokers, former smokers and never smokers. We evaluated trends in demographics, treatment modalities and outcomes in these 3 groups from 1999 to 2007. Results: The study population comprised a total of 63, 015 patients admitted to hospital with an ACS and with identifiable baseline smoking status. Smokers presented with STEMI more often than non-smokers. There was an unadjusted decline in 30-day mortality in all 3 groups. However, the adjusted decline was not statistically significant among current smokers (HR = 0.98 per study year, 95% CI 0.94–1.01, p = 0.20). A subgroup analysis of 22, 894 STEMI patients demonstrated no reduction in annual adjusted 30-day mortality rates among smokers (HR = 1.01, 95% CI 0.96–1.06 (Table 5), whereas former and never smokers' mortality declined. Conclusions: Over the years 1999–2007, 30-day mortality declined in patients presenting with acute coronary syndrome. However, smokers presenting with STEMI did not demonstrate a reduction in mortality.